Impact of Public-Private Partnerships on Private School Performance : Evidence from a Randomized Controlled Trial in Uganda - Barrera-Osorio, Felipe; de Galbert, Pierre; Habyarimana, James; Sabarwal, Shwetlena (World Bank, Washington, DC, 2017)
This paper estimates the short-term, partial-equilibrium impacts of a public-private partnership program for low-cost private secondary schools in Uganda. The public-private partnership program is part of a broader strategy to absorb large increases in secondary enrollment following the introduction of universal secondary education. Under the program, the government offers a per-student subsidy to participating private schools. Program implementation allowed for a randomized phase-in study design to estimate the causal impacts of the program on private school performance. The study finds that the public-private partnership program helped absorb large numbers of eligible students in secondary schools. Student performance in participating private schools was significantly better than in nonparticipating private schools. The study finds that improved student performance is potentially linked to increased input availability, as well as positive selection of government aided students in private schools. Suggestive evidence indicates that this selection most likely occurs on the part of households rather than schools.